(untitled) (Journal of Shaheed Suhrawardy Medical College, 2023)
Association between primary hyperparathyroidism and acute pancreatitis is very rare. We report a case of a 45-year-old female presented with acute pancreatitis. Primary hyperparathyroidism was diagnosed after that episode of pancreatitis. She had no additional risk factor for pancreatitis. It’s been 10 months after her successful parathyroid surgery, there has been no recurrence of abdominal pain and her serum calcium is within normal limits. The purpose of reporting this specific case is that this pathology is uncommon in occurrence and indicates the importance of keeping in mind all the causes of pancreatitis before declaring it as idiopathic. J Shaheed Suhrawardy Med Coll 2022; 14(1): 65-67